Vaccination Against Diphteria: An Example from the History of Preventive Medicine - DOĞAN, Hanzade; HOT, İnci; KESMEZACAR, Özgü (Cerrahpaşa Medical Journal, 2014)
Preventive medicine has always been more valuable than alternatives of treatment as, it prevents people from suffering and side effects of treatments. Vaccinations have been important tools of preventive medicine. Research about those topics have always existed through different ages of medical history. In this work of ours, we will study the details of the struggle against diphteria through history. Our major reference is the 'Journal of Health' (S›hhiye Mecmuas›) which was published in 1925. We will discuss the Findings in a comparative manner.